THE DEVELOPMENT A LEARNING MANAGEMENT MODEL WITH CO-OPERRATION LEARNING STAD TECHNIQUES ON THE INVENTION OF THE MUSICAL COMPOSITION MARCH WIENGSA SCHOOL WITH MANOHRA PHONEMES BY USING SIMPSON’S PRACTICAL SKILL FOR STUDENTS IN GRADE 3, WIENGSA SCHOOL - Tueksuban, Suchaya (Journal of MCU Nakhondhat, 2023)
This article of this study was: 1) Compare the student’s visual arts achievement in learning about the invention of the Marsh School music composition with Nora phonetic theme. Between the experimental group and the control group, 2) Compare the dance practice skills for students in learning about the invention of the Marsh School Music Composition with Nora Dimension. Between the experimental group and the control group. And 3) The development a learning management model with co-operative learning, STAD technique on the invention of the musical composition march Wiengsa school with Manorah phonemes by using Simpson’s practical skills for students in grade 3 at Wiengsa school. The qualitative research by us the tool as a questionnaire. Select purposive sampling such as: students in grade 3/9 and 3/10 at Wiengsa school in the basic dance course, semester 2, academic year 2022 for all 87 persons. Using analyzed with frequency statistics, percentage, average, standard deviation, independent t-test assumptions and Pearson’s Product Moment Correlation Coefficient. The results of the research were as follows: 1) Comparing learning achievements in dancing arts of students. There were scores from the post-test test of the experimental group (𝑥̅ = 25.37, S.D.= 1.90) and the control group (𝑥̅ = 20.44, S.D.= 2.68), and the evaluation of practical skills was significantly higher than the control group, statistical at the 0.05 level, 2) Compare the dance practice skills for students. There was learning achievement between the experimental group and the control group with t test statistics t = 10.219, were statistically significant at 0.05. And 3) The development a learning management model with co-operative learning, STAD technique on the invention, there are 6 components: principles, concepts, theories Principles of learning management learning process learning support Evaluation and sharing success.